2011
DOI: 10.1186/1476-4598-10-119
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 as an independent prognostic marker for survival of patients with non-adenocarcinoma subtype of non-small cell lung cancer

Abstract: BackgroundExpression of transglutaminase 2 (TGase 2) is related to invasion and resistance to chemotherapeutic agents in several cancer cells. However, there has been only limited clinical validation of TGase 2 as an independent prognostic marker in cancer.MethodsThe significance of TGase 2 expression as an invasive/migratory factor was addressed by in vitro assays employing down-regulation of TGase 2. TGase 2 expression as a prognostic indicator was assessed in 429 Korean patients with early-stage non-small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In ccRCC, TGase 2 specifically interacts with p53 to promote oncogenesis. Although the roles of TGase 2 in cancer are well studied, the subgroup of TGase 2-positive patients in specific cancer types is small [63]. Therefore, from a therapeutic point of view, TGase 2 is commonly considered a chemo-sensitizing target instead of an anti-cancer therapeutic target [42].…”
Section: Tgase 2 In Cancer Tissuementioning
confidence: 99%
“…In ccRCC, TGase 2 specifically interacts with p53 to promote oncogenesis. Although the roles of TGase 2 in cancer are well studied, the subgroup of TGase 2-positive patients in specific cancer types is small [63]. Therefore, from a therapeutic point of view, TGase 2 is commonly considered a chemo-sensitizing target instead of an anti-cancer therapeutic target [42].…”
Section: Tgase 2 In Cancer Tissuementioning
confidence: 99%
“…11 Increased expression of TGM2 is reported to be a negative prognostic marker in multiple cancers. 1922,43 Although a relationship to patient outcome was not found in our analyses, increased TGM2 was associated with higher tumor stage and poor differentiation indicating tumors overexpressing TGM2 may be more proliferative or aggressive. We observed higher TGM2 in EAC showing inflammatory and desmoplastic response (Table 1) and thus may be influenced by these processes.…”
Section: Discussionmentioning
confidence: 53%
“…In breast cancer and in non–small-cell lung cancers, TGM2 promoter hypermethylation seem to influence TGM2 expression and chemosensitivity. 19,38 In neuroblastoma cells, treatment with a histone deacetylase inhibitor increased expression of both the short and long isoforms of TGM2 , rendering them more resistant to chemotherapy treatment. 39 We therefore treated OE19 and OE33 EAC cell lines with the methylation and histone deacetylase inhibitors, 5-aza-2-deoxycytidine and trichostatin A, respectively, and examined their effect on TGM2 mRNA expression using qRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adenocarcinoma, unlike in squamous cell lung cancer, various kinds of driver mutations have been studied and various treatment options exist. In a previous study, TG2 was revealed to be a significant prognostic factor in squamous lung cancer (30). It is therefore necessary to study TG2 in the setting of squamous NSCLC.…”
Section: Discussionmentioning
confidence: 95%